Chronic embedded cortico thalamic closed loop deep brain stimulation for the treatment of essential tremor - Opri, E; Cernera, S; Molina, R; Eisinger, RE; Foote, KD; Okun, MS; Denison, T; Gunduz, A (American Association for the Advancement of Science, 2020)
Deep brain stimulation (DBS) is an approved therapy for the treatment of medicallyrefractory and severe movement disorders. However, most existing neurostimulators can only apply continuous stimulation (open-loop DBS, OL-DBS), ignoring patient behavior and environmental factors, which consequently leads to an inefficient therapy, thus limiting the therapeutic window. Here, we established the feasibility of a self-adjusting therapeutic DBS (closed-loop DBS, CL-DBS), fully embedded in a chronic investigational neurostimulator (Activa PC+S), for 3 patients affected by essential tremor (ET) enrolled in a longitudinal (6 months) within-subject crossover protocol (DBS OFF, OL-DBS, CL-DBS). Most patients with ET experience involuntary limb tremor during goal-directed movements, but not during rest. Hence, the proposed CL-DBS paradigm explored the efficacy of modulating the stimulationamplitude based on patient-specific motor behavior, suppressing the pathological tremor ondemand based on a cortical electrode detecting upper-limb motor activity. Herein, we demonstrated how the proposed stimulation paradigm was able to achieve clinical efficacy and tremor suppression comparable with OL-DBS in a range of movements (cup reaching, proximal and distal posture, water pouring, writing), while having a consistent reduction in energy delivery. The proposed paradigm is an important step towards a behaviorally modulated fully embedded DBS system, capable of delivering stimulation only when needed, and potentially mitigating pitfalls of OL-DBS, such as DBS-induced side effects and premature device replacement.